UJI VALIDITAS CAPM PADA PASAR MODAL BERKEMBANG: STUDI KASUS INDONESIA - Agusalim; Nikita Valentin; Selpi Julianti (Journal of Islamic Economics and Finance, 2025)
Capital markets in developing countries, including Indonesia, face various obstacles in applying the Capital Asset Pricing Model (CAPM), commonly used to analyze the relationship between risk and return. This study aims to test the validity of the CAPM in the Indonesian capital market and compare it with capital markets in developed countries. This study uses a Systematic Literature Review (SLR) approach, examining various studies related to the CAPM in developing markets and the factors that influence the model's accuracy. The study shows that the validity of the CAPM in developing capital markets is limited, primarily influenced by exchange rate variables, market volatility, and differences in economic conditions compared to developed markets. Evaluation of the risk-return relationship and investor risk profiles provides the basis for investment recommendations that are more appropriate to market conditions.The CAPM cannot be fully applied validly in developing markets like Indonesia, requiring model adaptations and investment strategies that take local factors into account to improve prediction accuracy and the effectiveness of investment decision-making.